Investigation of the effect of radiofrequency-electromagnetic field (RF-EMF) composed of mobile phone on brain EEG delta rhythms (Annals of Medical Research, 2021)
Aim: The widespread use of mobile phones causes concern. The purpose of the study was to evaluate the effect of talking on the mobile phone for a short time on the brain EEG delta wave.Material and Methods: A total of twenty healthy medical students were included in the study. Bipolar EEG recordings of experimental and control groups were obtained in the study. For EEG delta wave, domain measurements, fast fourier transform (FFT) and power spectral density (PSD) analyzes were evaluated with the SPSS program.Results: As a result of the study, the values of the mean delta wave of all variables (value, FFT max, FFT max F, PSD Max F and PSD Max Power) were given between those using and not using mobile phones. There was a significant change in the EEG delta value (p0.05).Conclusion: Short-term cell phone exposures did not cause any significant change in frequency and power spectral densities, which may cause changes in delta value. However, long-term effects should be examined and studies are needed to monitor possible changes of the EEG recording during the phone call.
Keywords: EEG; electromagnetic field; delta; mobile phone; radiofrequency